Optimalisasi Sampah Melalui Teknologi Biopori di Kelurahan Kota Besi Hilir - Muhammad Fauzan; Sritanti; Dina Kumala Sari; Lutfi Almadani; Desi Lestari; Khalimatus Sa'diah; Risa Amanda (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
In waste management, the general practice in many villages still focuses on landfilling waste which is then thrown into final disposal sites. Apart from that, burning waste is often used as an alternative to reduce the volume of existing waste. However, this method causes negative environmental impacts such as increased air pollution and soil damage around village areas. This article, with the title "Optimizing Waste Through Biopori Technology in Kota Besi Hilir Subdistrict", will explain how biopori technology can be an effective solution in dealing with waste management issues in this subdistrict. Biopori technology works by speeding up the process of decomposing waste and turning it into compost that is useful for farmers and local communities. The approach applied in this project consists of two phases: first, a persuasive approach, which involves outreach to increase public awareness and interest regarding biopore holes; second, a practical approach, where students are directly involved in the process of making biopore holes. From the results of this activity, a biopore hole has been installed as an example that can be adopted and further developed by the community. Apart from that, solid organic fertilizer is produced that can be used by farmers, and there has been a change in mindset in the way people manage their waste.